Languages of Religious writing on the Territory of the Grand Duchy of Lithuania (17th c.). Bilingual Postil by Konstantinas Sirvydas - Rutkovska, Kristina (Slavistica Vilnensis, 2018)
[full article, abstract in Polish; abstract in Lithuanian and English]The Grand Duchy of Lithuania (GDL) was known in the European culture as a multilingual and multicultural country. The history of Lithuanian language, especially its religious literature, was complicated: the first pieces of literature in Lithuanian appear only in the 16th century. The object of the current paper is the function of Lithuanian language and the extent of using other languages, first of all, Polish, in Catholic religious literature on the territory of the GDL. The paper provides an overview of general linguistic-cultural background, which stimulated writing in ethnic languages on the territory of the GDL, and the detailed presentation of the piece of literature, which is important to Lithuanian culture – the first original postil written in Lithuanian and Polish – the book of sermons “Gospel Points” by Konstantinas Sirvydas.Sivydas’ postil is a piece of literature which is very typical of its epoch, having the critical apparatus characteristic to this epoch, with a very concrete function of all the three languages: Lithuanian, Polish and Latin. The instrumental function in the postil is performed by the Lithuanian text, having to serve the priests in their pastoral work and ensure a closer contact with the believers. The Polish translation was aimed at the priestės whose knowledge of Lithuanian was weak. The Latin text includes indices, reflecting the contents of the postil, and the abbreviations providing references to the biblical excerpts, cited in the postil, and had to pass its contents to all those who knew Latin and thus could understand the value of the postil.Two columns of Lithuanian and Polish texts are basically of equal volume. Both parts of the postil have few disproportions, which mainly include: longer text excerpts in Polish, more common biblical abbreviations and references in the Polish version, differences in the citation layer, differences in the author’s layer of the text. It shows the method of sermons’ writing and the rules of translation into Polish used by Sirvydas.The Gospel Points have a very intensive Latin layer, which makes the book distinct from Polish relicts of the 16th and 17th centuries and the pieces of literature translated into Lithuanian. The polonisation of biblical abbreviations has been present in Polish religious literature since the times of the Brest Bible (1563; BB). In the Bible of Jakub Wujek and his postils, marginal notes are also written in Polish. However, it looks slightly different in the case of the translations into Lithuanian. Both Wujek’s postil, translated into Lithuanian, and Rej’s postil feature the lack of stability in the field of marginal notes. The presence of Latin in Sivydas’ sermons can be derived from the fact that the main source of the translation of the biblical citations was the Latin Vulgate.The existing research on Lithuanian postillography provides little information on the formation of the biblical style in Lithuania of that time. None of the existing homiletic pieces of the 17th century have been systematically analysed from this perspective. The analysed text of Sirvydas’ postil shows that writing the excerpts of his own sermons, Sirvydas tried to use the means of native language to express the complex religious contents. He commonly used spoken language expressions, emerging from a variety of folk Lithuanian language. However, the efforts to create abstract lexis, the formation of terminological-like structures, and the application of rhetoric rules is noticeable as well. It can be observed that this process of the formation of Lithuanian religious language was influenced by Latin and Polish languages.
Keywords: postyllography, languages of religious writing, Grand Duchy of Lithuania, Sirvydas